IMPLEMENTASI KEBIJAKAN PASPOR ELEKTRONIK 100% DALAM RANGKA MEMENUHI STANDAR INTERNASIONAL DOKUMEN PERJALANAN - Haya, Fadhila; Ryanindityo, Mochammad; Nurkumalawati, Intan (Polteknik Imigrasi, 2025)
The implementation of the 100% electronic passport policy is a strategic step by the Directorate General of Immigration in meeting international standards of travel documents in accordance with the provisions of the International Civil Aviation Organization (ICAO). This research aims to analyze the policy implementation process, as well as identify the challenges faced in its implementation. This research uses a descriptive qualitative approach with a literature study method. The results showed that the policy implementation was carried out in stages starting December 1, 2024 at 13 immigration offices in Indonesia. The advantages of electronic passports include high security, efficiency of the immigration process, and ease of visa application. However, challenges remain, such as infrastructure gaps between cities and regions, lack of technical training for officers, and uneven public understanding of the benefits of electronic passports. Overall, this policy reflects a response to the global need for secure and efficient travel documents amidst the evolving dynamics of international mobility.